The Choice Of Place And Product Availability To Retail Business Continuity - Andrian Andrian; Supardi Supardi (JIMF (Jurnal Ilmiah Manajemen Forkamma), 2021)
The research aims to know whether retail business can struggle against the situation nowadays. Ones of the most important factors when running a business are location and product availability. One of the largest franchise networks in Indonesia is PT. Lion Super Indo (Superindo Stores). The research was conducted in two Superindo stores located in Bekasi Timur Sub-district by giving questionnaires to 200 respondents/consumers. The research methodology used was descriptive quantitative and multiple linear regression analysis. The results of this study are that Choice of Place variable has a negative and no significant effect on Business Continuity while Product Availability variable has a positive and significant effect on Business Continuity. The uniqueness of this study is that Business Continuity variable can be affected by Product Availability variable of  4.7% of the other factors.